Determination of different arsenic species in food‐grade spirulina powder by ion chromatography combined with inductively coupled plasma mass spectrometry. Issue 18 (31st August 2017) - Li, Xiangmei; Chen, Yuxi; Ye, Jun; Fu, Fengfu; Pokhrel, Ganga Raj; Zhang, Huang; Zhu, Yongguan; Yang, Guidi
Abstract: A "two‐step" pressurized microwave‐assisted extraction method coupled with ion chromatography with inductively coupled plasma mass spectrometry for the determination of different arsenic species in spirulina samples was developed. The extraction method used H2 O2 /H2 O (1:5, v/v) as solvent to extract all arsenic species except arsenite, which was extracted by using water as solvent. The extraction method had a satisfactory recovery (>96%) and took a short time (20.0 min). With our method, all arsenic species in spirulina samples were completely separated and determined with recoveries of 84–105% and relative standard deviations of 2–4%. Food‐grade spirulina powder samples from seven provinces (Inner Mongolia, Zhejiang, Fujian, Hainan, Yunnan, Jiangsu, and Guangxi) in China were analyzed using the optimized protocol. Arsenate was detected at the concentration range of 170–394 ng/g in all the spirulina samples. Dimethylarsinic acid was detected at the concentration range of 32–839 ng/g in spirulina from above‐six provinces except Guangxi. Monomethylarsonic acid (67 ± 3 ng/g) was detected only in spirulina from Yunnan province. Arsenite was detected at the concentration range of 28–147 ng/g in spirulina from above five provinces except Hainan and Guangxi. Five unknown organic arsenic species were found in spirulina from above six provinces except Guangxi.